Effect of Canopy management practices on growth and yield of potato in Net house - Devi, Sugani (Potato Journal, 2018)
The advent of Hi-tech seed production systems, where propagation carried out under controlled facilities like tissue culture labs, net houses and aeroponic units has opened a new arena offering immense possibilities for increasing the productivity of potato crop. As a result of that for multiplication of early seed generations under insect proof net house has been rapidly adapted by the farmers. However, several biotic and abiotic factors limit the potato tuber yield there are more number of undersize tubers under net house. Overcrowding of branches, less circulation of air and poor light inside the canopy are related abiotic factors which indirectly affect productivity. Plant lodging, poor aeration and light penetration cause the leaves to turn yellow and fall on ground, leading to significant decrease in photosynthesis. The compact canopy also harbours various pests and disease causing agents due to favourable micro-climate in canopy. .An experiment was designed to study the effect of new canopy management approaches on overall potato seed productivity using Single and Double layer canopy netting system which keeps plants upright. Three varieties viz., Kufri Pukhraj, Kufri Gaurav and Kufri Chipsona-1, were planted in 3 replicationsin flat beds at 10 X 10 cm spacing. Growth and yield characters like plant height, number of yellow leaves, number of nodes, number of tubers harvested and yield were recorded. Number of undersized tubers (<3 g) were significantly reduced in both of the treatments in comparison to control in all the three varieties. On an average number of undersized tubers were reduced by 61.75% in double net and by 39.04% in single net over control. Number of undersized tubers in Kufri Gaurav reduced by 81.11% in double net system over control whereas in Kufri Chipsona-1 the reduction was about 57.14% over control. In Kufri Gaurav total weight of tubers in double and single netting system was increased by 35.16% and 22.18% respectively over control (CN)., whereas in Kufri Chipsona-1 yield increased by 47.17% in double net and 11.08% in single netting system over control. Based on the experiment it can be concluded that with canopy netting practices we can significantly reduce number of undersized tubers and overall tuber productivity and hence economy can be improved.